Pengaruh Hubungan antara Obesitas dan Merokok dengan Kejadian Hipertensi pada Lansia - Sekanya Ardhia Rezkita; Ari Mega Pratiwi; Ririh Yudhastuti (Universitas Airlangga, 2023)
Background: The background for this work hypertension is the silent killer or the silent disease because the sufferer does not know that he has hypertension. The incidence of hypertension in Indonesia has increased from the 2013 Riskesdas data, aged 55-64 years by 45.9%, increasing to 55.2% from the 2018 Riskesdas data. Objectives: State the objectives of this research This study aims to analyze the relationship between age, obesity and smoking with the incidence of hypertension in the elderly Methods: The methods employ in this research The type of research used is analytic observational with cross sectional research design. This study uses secondary data from the Indonesian Family Life Survey (IFLS) 5. The research sample is the entire elderly population (age > 60 years) totaling 1,050 respondents who have met the criteria. The variables studied obesity, and smoking. This study was univariate analysis and bivariate analysis using Chi-square. Results: The results showed that there was a relationship betweenobesity (p value = 0.000; PR = 0.46; CI = 0.37 - 0.58), and smoking (p value = 0.001; PR = 1.25; CI = 1.09 - 1.44) with the incidence of hypertension in the elderly. Conclusions: Obesity and smoking are variables associated with the incidence of hypertension in the elderly. Smoking are risk factors for hypertension, obesity is a protective factor for hypertension. Suggestions for this research are expected that the elderly community can implement healthy living behaviors, and the government can provide education regarding risk factors for hypertension in the elderly community.